Drosophila Infestations of California Strawberries and Identification of Drosophila suzukii Using a TaqMan Assay - Fatemeh Ganjisaffar; Antoine Abrieux; Brian E. Gress; Joanna C. Chiu; Frank G. Zalom (Applied Sciences, 2023)
In contrast to most other Drosophila species that infest processing (overripe) strawberries, the spotted-wing drosophila (SWD) can also infest firm and ripe fruit intended for the fresh market. However, fresh fruit infestations of this invasive species did not become an economic problem for California growers until a decade after SWD’s first detection in California strawberries in 2008. This outbreak corresponds to the development of reported insecticide resistance in SWD populations from strawberry and other berry crops following years of incidental exposure of insecticide applications against other key pests. The objective of this study was to determine the current levels of Drosophila infestation in fresh market and processing strawberries which would inform the choice of insecticides to use for control. We sampled fresh market and processing strawberries from 17 fields over a two-year period in the three major strawberry production areas of California and determined the numbers of emerged SWD and non-SWD Drosophila adult flies. In addition, since holding fruit for adult emergence to determine species composition is impractical for making rapid control decisions and could be inaccurate due to potential interspecific competitions among larvae in the fruit, we developed a TaqMan assay that facilitates larval identification.